2020
DOI: 10.1016/j.ijer.2020.101538
|View full text |Cite
|
Sign up to set email alerts
|

Building bridges in higher education: Student-faculty relationship quality, student engagement, and student loyalty

Abstract: This study's aim was to investigate a hypothesized model examining the associations between students' perceptions of the quality of their relationship with their educational faculty and staff (i.e., relationship quality) and students' involvement. The relationship quality measurement included students' experiences with all educational faculty and staff, with the aim of predicting student engagement and student loyalty. Based on data from 454 higher education students, findings indicate that affective commitmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
105
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(140 citation statements)
references
References 68 publications
8
105
0
1
Order By: Relevance
“…In the hypothesized and tested model, trust in benevolence had a statistically significant association with absorption, dedication, and vigor. In previous research (Snijders et al 2018b), where the sample consisted of enrolled students, trust in benevolence did not have a statistically significant association with student engagement. Perhaps alumni's perception of their former trust in faculty and staff's helpfulness changes over time.…”
mentioning
confidence: 64%
See 3 more Smart Citations
“…In the hypothesized and tested model, trust in benevolence had a statistically significant association with absorption, dedication, and vigor. In previous research (Snijders et al 2018b), where the sample consisted of enrolled students, trust in benevolence did not have a statistically significant association with student engagement. Perhaps alumni's perception of their former trust in faculty and staff's helpfulness changes over time.…”
mentioning
confidence: 64%
“…Qualitative research by Cotten and Wilson (2006) suggested that the frequency and quality of interactions between students and their faculty/staff could stimulate positive relationships between all parties. Recent research (e.g., Pianta et al 2012;Xerri et al 2018) has pointed out that students' perceptions of the relations between students and their faculty/staff can positively influence students' engagement, and in turn, students' current loyalty (Snijders et al 2018b;Sung and Yang 2009). For instance, in an earlier study (Snijders et al 2018b), findings indicated that affective commitment and affective conflict are important relationship quality dimensions that positively link with the student engagement of enrolled students.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Alioon and Delialioğlu (2019) explored the implementation of m-learning and their comparison of the results from two semesters revealed that the improvements in the immersive content of the activities and instructional process increase the collaboration among students as well as their interaction with the instructor leading to better academic performance. In this context adoption of online tools for education coupled with a relationship management approach to enhancing the relationship quality between students and instructors can help increase students' attendance and engagements (Snijders et al, 2020).…”
Section: Student Attendance and Engagementmentioning
confidence: 99%